Translocation of benzo(a)pyrene reactive metabolites across human mammary epithelial cell membranes - B. Alex Merrick; Ashley M. Brooks; Julie F. Foley; Betty K. Mansfield; James K. Selkirk (PLoS ONE, 2025)
DNA adducts from benzo(a)pyrene (BaP) and other polycyclic aromatic hydrocarbons (PAH) are related to tumor initiation in many tissues including mammary epithelia. T47D mammary cells are able metabolizers of BaP, forming DNA and cellular protein adducts but also a sizeable amount of extracellular protein adducts. GSH S-transferases (GST) help mitigate adduct formation by glutathione (GSH) conjugation. Here, we varied GSH levels using buthionine sulfoximine (BSO) and BaP pretreatments to deplete or augment GSH, respectively, to study adduct formation and metabolism at 4 µM 3 H-BaP over 24–48hr. An inverse relationship was observed between GSH levels and nuclear protein and DNA adducts. Time course experiments showed extracellular protein adducts, identified primarily as bovine serum albumin and α1-AT (α-1-antitrypsin) in culture medium, were 5–10 times greater than cellular protein adducts and comprised 8–9% of total metabolized 3 H-BaP. However, specific adduct binding (adducts/mg protein) in cells was much greater than for extracellular protein, likely from their intracellular proximity to CYP-mediated metabolism to BaP reactive metabolites. Proportions of 3 H-BaP hydroxylated and conjugated metabolites in BSO and BaP pretreated cells were not greatly altered from DMSO control after 24 hr. Bioinformatic analysis of T47D cell gene expression indicated CYP1B1 and CYP1A1 were primary enzymes for BaP bioactivation. We surmised reactive BaP metabolites that escaped conjugation reactions were sufficiently stable to migrate into the extracellular space. These results suggest BaP reactive metabolites like BPDE (BaP-diol-epoxide) can easily translocate across cell membranes despite robust conjugation systems and ready supplies of essential co-substrates for sulfate or GSH conjugations. The implications in vivo are that BaP reactive metabolites can enter adjacent epithelia and some fraction could result in DNA binding and somatic mutations in cancer susceptibility genes over time. The relationship continues to grow between PAH exposure and pollution, and many malignancies including breast cancers.